Modeling and experimental verification of the thin multi-electrode piezoceramic bars’ forced vibrations - Bezverkhy, O. I.; Zinchuk, L.P.; Karlash, V. L. (Publishing House of Lviv Polytechnic National University, 2016)
This paper is devoted to analysis of the multi-electrode piezoceramic bars’ forced vibrations. Analytical model is built for a thin and narrow piezoelectric ceramic bar with three pairs of divided electrodes on the upper and lower main surfaces. The formulae for input admittance, characteristic (resonant and anti-resonant) frequencies as well as for transform ratio are obtained. The fundamental modes of vibrations of thin piezoelectric bar and their odd and even overtones are studied. A new experimental simple technique with additional commutation permits to study many resonators’ parameters: admittance, impedance, phase angles, power components etc. Experiments have been carried out with TsTBS-3 bar-prism70.3×8.1×6.8/7.1 mm size. It is established that a high electromechanical coupling may be obtained for bar’s longitudinal overtones by means of the electrode coating dividing and anti-phase electrical loading. In partly shorted electrodes case, not only odd but even longitudinal modes can be induced, which are absent for full electrodes case. Стаття присвячена аналiзу вимушених коливань багатоелектродних п’єзокерамiчних стрижнiв. Аналiтична модель побудована для тонкого й вузького п’єзокерамiчного стрижня з трьома парами роздiлених електродiв на горiшнiй i нижнiй основних по- верхнях. Отриманi формули вхiдного адмiтансу, характеристичних (резонансних i антирезонансних) частот, а також коефiцiєнтiв трансформацiї. Дослiджувались основнi моди коливань i їхнi парнi та непарнi обертони. Нова проста експериментальна методика з додатковою комутацiєю дає змогу вивчати багато параметрiв резонатора: адмiтанс, iмпеданс, фазовi кути, компоненти потужностi тощо. Експерименти велися iз стрижнями-призмами розмiром 70.3 × 8.1 × 6.8/7.1 мм iз керамiки ЦТБС–3. Встановлено, що високий електромеханiчний зв’язок на обертонах поздовжнiх коливань стрижня можна отримати шляхом роздiлення електродного покриття i протифазного електричного навантаження. У випадку коротко замкнутих окремих електродiв можуть збуджуватися не тiльки непарнi, а й парнi поздовжнi моди, яких при суцiльних електродах немає.
Моделювання й експериментальна верифiкацiя вимушених коливань тонких багатоелектродних п’єзокерамiчних стрижнiв
Keywords: multi-electrode piezoceramic bar; forced vibrations; electromechanical coupling; input admittance; transformation ratio; багатоелектродний п’єзокерамiчий стрижень; вимушенi коливання; електромеханiчний зв’язок; вхiдна провiднiсть; коефiцiєнт трансформацiї